UNFAIR COMPETITION IN PATENT LAW (PATENT TROLLING) - Diduk, Alla; Lytvyn, Stepan; Pysanyy, Roman (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
The purpose of this article is to consider problematic issues regarding unfair competition in patent law, in particular, patent trolling. For this purpose, the concepts of «patent trolling» and «patent troll» were analyzed. Types of patent trolls are also defined. The signs and peculiarities of patent trolling in Ukraine and the reasons for its spread are established. The manifestation of unfair competition, consisting in the abuse of intellectual property rights, is considered. Recommendations are given on introducing an effective mechanism to combat patent trolls and bring them to justice for unfair competition. The methodological basis of the research is general scientific and special methods of scientific knowledge. The use of these methods made it possible to describe and propose ways to solve the problem of unfair competition in patent law, in particular, patent trolling. Results: no provision in national legislation directly provides for the liability of patent trolls for abuse of rights, including under competition law. Ukrainian legislation does not provide for the liability of patent trolls for the abuse of rights, which in a certain way have a conditional nature, since they are provided under their personal responsibility in terms of compliance of the object with the conditions of patentability or the criteria of protectionability. In this regard, it is necessary to eliminate the causes and conditions that contribute to the mentioned negative phenomenon at the legislative level. Discussion: in fact, «patent trolls» are neither product manufacturers nor inventors, but only possess property rights to objects of intellectual property rights, buying up protective documents for them and realizing these rights only by prohibiting their use, initiating lawsuits, in fact, that’s why they got that name.